Variation of parameters question

Can someone help get me started with this I'm not sure where to begin..

$\displaystyle

\begin{gathered}

x\frac{{dy}}

{{dx}} + (2 + 3x)\frac{{dy}}

{{dx}} + 3y = r(x); \hfill \\

\hfill \\

Solution \hfill \\

y = 1/x \hfill \\

with \hfill \\

r(x) = 0 \hfill \\

\end{gathered}

$

Form

$\displaystyle

y(x) = \frac{1}

{x}v(x)

$

and I need to find the complete general equation corresponding to

$\displaystyle

r(x) = 3e^{ - 3x}

$

Can someone get me started with this.. do I differentiate y(x) part and substitute that into the equation?(Wondering)